Indigenous suicides in Valle del Cauca, Cauca and Nariño (Colombia) before (2018-2019) and during the COVID-19 pandemic (2020-2021) - Charry Lozano, Liliana (2023)
Introduction: The Center for Disease Control and Prevention (CDC) defines suicide as an act of self-harm with the intent to cause a voluntary death. In indigenous peoples from countries such as Canada, Australia, Greenland, the United States, New Zealand, Brazil and Siberia, it is evident that this event occurs more frequently than in the general population, mainly as a consequence of colonialism and difficulties faced by indigenous communities, factors that are now considered as common throughout the world. Methods: A retrospective, descriptive, quantitative and retrospective study that analyzes 48 cases of suicide in indigenous people from Southwestern Colombia during the COVID-19 pre-pandemic (2018-2019) and pandemic (2020-2021) periods and registered in the National Institute of Legal Medicine and Forensic Sciences of the departments of Valle del Cauca, Cauca and Nariño. Results: In the studied region more people committed suicide during the pandemic period (2020-2021). The victims were, predominantly, males of young ages (between 19 and 26 years), with a primary and high school educational level, of primary and high school, with farmer or student occupations, use of hanging as the main modality, and conflict with partner or ex-partner as the most frequently cited reason. Conclusions: The suicide rate among indigenous people in the departments of Cauca Valley, Cauca and Nariño was higher than that recorded in the general population of the same departments during the COVID-19 pandemic (2020-2021). It is necessary to consider sociocultural factors and the trajectories of the suicide event within each distinctly studied community.